Time evolution of the South Atlantic Magnetic Anomaly - Gelvam A. Hartmann; Igor G. Pacca (Anais da Academia Brasileira de Ciências, 2009)
The South Atlantic Magnetic Anomaly (SAMA) is one of the most outstanding anomalies of the geomagnetic field. The SAMA secular variation was obtained and compared to the evolution of other anomalies using spherical harmonic field models for the 1590-2005 period. An analysis of data from four South American observatories shows how this large scale anomaly affected their measurements. Since SAMA is a low total field anomaly, the field was separated into its nondipolar, quadrupolar and octupolar parts. The time evolution of the non-dipole/total, quadrupolar/total and octupolar/total field ratios yielded increasingly high values for the South Atlantic since 1750. The SAMA evolution is compared to the evolution of other large scale surface geomagnetic features like the North and the South Pole and the Siberia High, and this comparison shows the intensity equilibrium between these anomalies in both hemispheres. The analysis of non-dipole fields in historical period suggests that SAMA is governed by (i) quadrupolar field for drift, and (ii) quadrupolar and octupolar fields for intensity and area of influence. Furthermore, our study reinforces the possibility that SAMA may be related to reverse fluxes in the outer core under the South Atlantic region. A Anomalia Magnética do Atlântico Sul (SAMA) é uma das maiores anomalias do campo geomagnético. A variação secular da SAMA foi obtida e comparada com a evolução de outrasanomalias usando modelos de campo por harmônicos esféricos para o período de 1590-2005. Uma análise dos dados de quatro observatórios da América do Sul mostra como esta anomalia de grande escala afetou suas medidas. Como a SAMA é uma anomalia de campo total baixo, o campo foi separado nas componentes não-dipolar, quadrupolar e octupolar. A evolução temporal das razões dos campos não-dipolar/total, quadrupolar/total e octupolar/total mostram valores elevados para o Atlântico Sul desde 1750. A evolução da SAMA é comparada com a evolução de outras grandes feições geomagnéticas de superfície como os pólos ...